Dinamika Resistensi Antimikroba dan Dampak Ekotoksikologi Limbah Cair Rumah Sakit terhadap Ekosistem - Kartini Amelia Putri; Mirryazil Jannah; Nadisa Azzahra; Firdus Firdus; Muhammad Nasir; Alia Rizki (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Antimicrobial resistance and environmental pollution from hospital wastewater are global problems that threaten human health and ecosystems. Wastewater from healthcare facilities contains pathogenic microorganisms, antibiotic residues, resistance genes, as well as chemical pollutants that cannot be completely removed by conventional waste treatment systems. The research method was conducted based on a literature review, including experimental approaches, field surveys, and literature studies. The results of the study indicate that the presence of biofilms in drainage channels serves as a major reservoir for multi-drug resistant (MDR) bacteria and facilitates horizontal transfer of resistance genes, accelerating the emergence of increasingly resistant microbial strains. Non-antibiotic pollutants such as analgesic drugs and caffeine also affect the composition of the wastewater microbiome and increase the risk of pathogen growth and resistance. The toxicological impacts of this pollution can cause oxidative stress and tissue damage in aquatic organisms, as well as serious problems in the food chain cycle. Conventional waste treatment often cannot filter all residues and resistance genes, thus requiring the application of more advanced treatment technologies such as advanced oxidation and the use of nanomaterials. To reduce this risk, hospital waste management must be conducted systematically and scientifically, including controlling the rational use of antibiotics and improving the effectiveness of wastewater treatment systems. This approach is important to protect public health, maintain the sustainability of aquatic ecosystems, and prevent the widespread spread of antibiotic resistance.